Techniki obrazowaniaOwn experience in application of the dual source computer tomography for epicardial coronary arteries evaluation in the transplanted heart: a pilot study - Wierzbicki, Karol; Przybyłowski, Piotr; Klimeczek, Piotr; Milaniak, Irena; Banyś, Robert P.; Węgrzyn, Piotr; Sobczyk, Dorota; Krupiński, Maciej; Pasowicz, Mieczysław; Sadowski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background: Graft vasculopathy is still one of the most important limiting factors for long-term survival after heart transplantation (HTX). Standard diagnostic methods of vasculopathy are invasive procedures: coronary angiography and intravascular ultrasound (IVUS). Aim: Evaluation of feasibility of a non-invasive test, i.e. the Dual Source Computed Tomography (DSCT) in the assessment of epicardial coronary arteries stenoses in the transplanted heart. Material and methods: DSCT was performed in 15 patients (12 males, 3 females), age between 37 and 75 years, mean age 57.5 ±10.2 years, being followed-up between 3 and 17 years, on average 11.6 ±3.5 years after heart transplantation. Results: 202 segments of epicardial coronary arteries were assessed altogether in 15 patients after HTX (average 13 seg-ments/pts). DSCT imaging allowed diagnosis of typical vasculopathy changes in 7 patients. The standard atherosclerosis was predominant in 4 patients. In 4 patients, DSCT revealed mixed changes. Conclusions: DSCT is a safe, well-tolerated and reliable tool in the qualitative and quantitative assessment of epicardial coro-nary arteries of the transplanted heart.